2021
DOI: 10.3390/ijerph182413307
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Carbon Emission Reduction Effect of the Air Pollution Prevention and Control Action Plan in China

Abstract: In this study, we propose an integrated econometric framework incorporating the difference-in-differences model, the propensity-score-matching difference-in-differences model, and the spatial difference-in-differences model to explore the effect of the Air Pollution Prevention and Control Action Plan on per capita carbon emission in China at the national, regional, and administrative levels. Contradictory results are supported under different econometric models, which highlight the importance and necessity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The advantage of this approach is that it can estimate the effect of a specific intervention or treatment by comparing changes in outcomes over time. Many scholars used the DID method to investigate China's clean winter heating policy (Weng et al, 2021;Weng et al, 2022) and air pollution control policy (He et al, 2020;Zhang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of this approach is that it can estimate the effect of a specific intervention or treatment by comparing changes in outcomes over time. Many scholars used the DID method to investigate China's clean winter heating policy (Weng et al, 2021;Weng et al, 2022) and air pollution control policy (He et al, 2020;Zhang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The processing variable is set as whether an enterprise is in the published PITI area. To eliminate the biased estimation results caused by sample self-selection, propensity score matching (PSM) was used to process the samples [ 33 ]. Taking the total industrial water consumption of each enterprise as the response variable, the benchmark multi-period DID Model (1) was obtained as follows: …”
Section: Methodsmentioning
confidence: 99%
“…The existing studies about manufacturing emissions mostly conducted index decomposition analysis at the national level or the provincial level. Only a few studies have investigated the emissions at the city level [ 20 , 21 , 22 ] and have focused on Beijing, Shanghai, Tianjin, Chongqing, and Zhuhai in China [ 23 , 24 ]. Gu et al studied the determinants of Shanghai’s CO 2 emission change during the period 1995–2015 and identified that energy intensity is the main factor for carbon mitigation, followed by economic structure, residential energy intensity, and emission coefficients [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%